Gender differences in the psychophysiological effects induced by VOCs emitted from Japanese cedar (Cryptomeria japonica) - Eri Matsubara; Shuichi Kawai (Komiyama Printing Co. Ltd, 2018)
Abstract Background Wood is a valuable material for interiors, and the psychophysiological relaxation effects of volatile organic compounds (VOCs) from wood chips and essential oils have been reported. However, few studies have identified the odors in full-scale wooden environment, and also, differences in gender have not been clarified. In this study, we aimed to confirm the effects of VOCs emitted from interior wood walls in both human male and female participants. Methods We used Japanese cedar timber and analyzed VOCs in the experimental rooms with and without Japanese cedar timber by gas chromatography-mass spectrometry (GC-MS). The physiological effects were measured using neuroendocrinological and immunological parameters in saliva. A questionnaire was used to evaluate the subjective responses to each odor in the experimental rooms. Results The main compound emitted from Japanese cedar timber was δ-cadinene, and the total volume of VOCs in the wood condition (presence of VOCs emitted from Japanese cedar) was 282.4 (μg/m3). Significant differences between genders in salivary parameters were shown that there were decreases of α-amylase in wood condition and increases of cortisol in the control (absence of VOCs) condition in female participants compared to male participants. The results demonstrated that VOCs in the experimental room with Japanese cedar timber tend to suppress the activation of the sympathetic nervous activity and non-VOCs of Japanese cedar in the control room increase cortisol in female participants. Conclusions These results suggest that an indoor environment with wood interior materials has the potential to be useful for health management, especially women's health.